Eco-Dying on ZnO Nanoparticles using Tamarindus Indica L. Seed Coat Tannin - Palamadathil, Shaniba; Thottoli, Abdul Kareem; Puthumana Melepattu, Sreelakshmi; Parambil, Shivina Nandhayil; Prakash, Athira; Mubarak K.P., Muhasin; Mannisheri, Labeeba; Al-Akraa, Islam M.; Mohammad, Ahmad M.; Che Halin, Dewi Suriyani; et al. (Archives of Metallurgy and Materials, 2026)
This study aims to explore the potential of Tamarindus indica L. seed coat tannin as a natural dye sensitiser for zinc oxide nanoparticles. The tannin extract was prepared by mixing ground seeds with de-ionised water and utilised as a natural dye to sensitise ZnO nanoparticles, enhancing their optical absorption properties in the visible region. ZnO nanoparticles were synthesised in the presence of varying concentrations of Tamarindus indica L. seed coat tannin to investigate its impact on their growth and optical behaviour. Results demonstrated that the Tamarindus indica L. seed coat extract contained abundant polyphenolic compounds with characteristic hydroxyl groups, confirming its suitability as a natural sensitiser, while Fourier-transform infrared spectroscopy indicated strong chemical interactions between tannin molecules and zinc oxide through Zn–O bonding. Ultraviolet-visible analysis revealed that tannin incorporation extended the optical absorption edge of zinc oxide nanoparticles from 400 to 800 nanometres, shifting it into the visible spectrum. X-ray diffraction confirmed a hexagonal wurtzite structure with an average crystallite size of approximately 17 nanometres, supported by transmission electron microscopy observations. These findings demonstrate that Tamarindus indica L. seed coat tannin effectively enhances the light-harvesting capability of zinc oxide nanoparticles, offering a sustainable, low-cost approach for improving the optical performance of zinc oxide-based materials in dye-sensitised solar cells and other optoelectronic applications.